2005
DOI: 10.1095/biolreprod.104.037895
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Vitellogenins (Vgs) in Mosquitofish (Gambusia affinis): Identification and Characterization of Three Functional Vg Genes and Their Circulating and Yolk Protein Products1

Abstract: The objectives of this study were to characterize multiple forms of vitellogenin (Vg) in mosquitofish (Gambusia affinis) and to discover the fate of each Vg during its processing into product yolk proteins. Two Vg preparations, with apparent masses of 600 kDa (600 Vg) and 400 kDa (400 Vg), were isolated from the plasma of fish treated with estradiol-17beta (E(2)) by various chromatographic procedures. Immunological analyses verified the presence of two different Vg proteins (600 VgA and 600 VgB) in the 600 Vg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 62 publications
(119 reference statements)
5
74
0
Order By: Relevance
“…To date, the complete Vtg (VtgA and/or VtgB) and incomplete Vtg (VtgC) have been successfully isolated and purified as two different proteins with distinct molecular weights and antigenicity in various fish species, including tilapia (O. aureus [85] and O. mossambicus [86]), medaka [87], Japanese goby Acanthogobius flavimanus [88] and Sakhalin taimen [89]. In addition, three distinct types of Vtg have been purified or detected in mosquitofish Gambusia affinis [90], red seabream Pagrus major [91] and grey mullet [92]. Two or three types of Vtgs have been detected as proteins with distinct antigenicity in various existing fish species [66].…”
Section: Multiplicity Of Fish Vitellogeninsmentioning
confidence: 99%
“…To date, the complete Vtg (VtgA and/or VtgB) and incomplete Vtg (VtgC) have been successfully isolated and purified as two different proteins with distinct molecular weights and antigenicity in various fish species, including tilapia (O. aureus [85] and O. mossambicus [86]), medaka [87], Japanese goby Acanthogobius flavimanus [88] and Sakhalin taimen [89]. In addition, three distinct types of Vtg have been purified or detected in mosquitofish Gambusia affinis [90], red seabream Pagrus major [91] and grey mullet [92]. Two or three types of Vtgs have been detected as proteins with distinct antigenicity in various existing fish species [66].…”
Section: Multiplicity Of Fish Vitellogeninsmentioning
confidence: 99%
“…As none of the above features fit to the aforementioned Vtg-related intermediate bands (bands migrating between ~62 to ~43 kDa), they might be proteolytic variants other than typical YP classes. A possible complex peptide composed of β′-c and Pv appeared to be present in the catshark (Yamane et al, 2013), while the presence of other YP variants with variable combinations of YP domains has been found in several fishes (Sawaguchi et al, 2005;Amano et al, 2007b). Thus, fishes may differ in the mode of Vtg cleavage, giving rise to a variety of Vtgderived YP peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to its deposition in yolk granules, Vtg undergoes limited proteolytic cleavage, giving rise to several classes of YPs. In teleosts, Vtg-derived YPs are typically designated as lipovitellin (Lv), phosvitin (Pv) and β′-component (β′-c) (Matsubara and Sawano, 1995;Hiramatsu and Hara, 1996;Hiramatsu et al, 2002b, c), while some other YP variants (e.g., Cterminal peptide and Lv-Pv complexes) are also evident Sawaguchi et al, 2005;Amano et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this assumption, heart tissue has often been overlooked to test for vtg mRNA levels in previous reports on medaka vtgAb, zebrafish vtgAo1, vtgC or many other newly cloned fish VTG transcripts (Wang et al, 2000;Islinger et al, 2003;Van der Ven et al, 2003;Tong et al, 2004;Wang et al, 2005;Jung et al, 2005;Sawaguchi et al, 2005;Mikawa et al, 2006). One exception is the report by Mikawa et al (2006) that indicated that vtgAe1 expression is not expressed in the heart tissue of the Japanese conger.…”
Section: Discussionmentioning
confidence: 99%